The geography of Milton Santos and the problem of the marxism of instances: a gramscian reading - da Silva, Marcos Aurelio; Engel Voigt, Mateus (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2021)
This article analyses the discussion that Milton Santos establishes with Louis Althusser in two works central to the theoretical formulations that he developed from the 1970s on. Its objective is to confront the structuralism of the French philosopher with the category of socio-spatial formation then proposed by the Brazilian geographer. Contrary to what has been established in the literature, the article’s conclusion points to a clear distancing between the two authors, since for Milton Santos the determinations of social transformation are not limited only to economic aspects, which still remain dominant in Althusser’s structuralism, but are instead the result of the totality of social relations, strictly speaking, socio-spatial relations. This approach draws the Brazilian geographer much closer to reflections such as those developed by Antonio Gramsci’s Marxism. Milton Santos; Louis Althusser; Antonio Gramsci; Socio-spatial formation; Social totality.